Public Management and Administration - Comite, Ubaldo (IntechOpen, 2018)
The public sector plays an important role for both regulation and in the delivery of services directly or indirectly. In this context, it is important to consider transformation, change, and innovation, which are the elements on which the main determinants that influence public management and the administration of economic, social, and political systems are based. This book describes the nature of the problem, its multidimensionality, and the need for original approaches, through the contribution of scholars belonging to different disciplines. This book contains nine chapters in a single section (Public Management and Administration), which, through the different approaches to the subject by the authors, help to explain the issues of the public sector.